Impact of high-speed railway on urban resilience in China: Does urban innovation matter? - Wang, Ke-Liang; Jiang, Wei; Miao, Zhuang (Socio-economic planning sciences, 2023)
Based on calculating the urban resilience index from five aspects of economy, society, institutions, infrastructure, and ecology by adopting the entropy method, this study applies the time-varying DID model to systematically examine HSR's impact on China's urban resilience, on basis of which its heterogeneities and the mediating effect of urban innovation are also quantified. The findings reveal that: (1) HSR can significantly promote China's urban resilience, as supported by various robustness tests. (2) HSR can significantly improve economic and institution resilience of cities, but does not play a significant role on social resilience and infrastructure resilience, and has a negative effect on ecological resilience. (3) The driving effects of HSR on the resilience of core cities, large cities, and non-resource-based cities are more significant. (4) Urban innovation is an important channel through which HSR impacts urban resilience. The conclusions of this study can offer useful insights for China's future HSR planning and resilient cities construction. •Study shows HSR boosts China's urban resilience, supported by robustness tests.•Economic/institutional resilience benefits, but ecological impact negative. Effects vary by city type.•Significant effects observed in core cities, large cities, and non-resource-based cities.•Urban innovation identified as an important mediating factor in the impact of HSR on urban resilience.